2000
DOI: 10.1016/s1471-0153(00)00008-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy and nutritional counseling in the treatment of bulimia nervosa and binge eating

Abstract: The goals of manual-based cognitive-behavioral therapy (CBT) and nutritional counseling for eating disorders are similar, namely, eliminating dysfunctional patterns of eating. Modifying these behaviors requires specific therapeutic expertise in the principles and procedures of behavior change that is not typically part of the training of nutritionists and dieticians or mental health professionals without specific expertise. We discuss ways in which principles of behavior change can be applied to eating disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…CBT treatments have the advantage over some other treatment approaches in that they are generally manual-based, meaning that non-psychologist health professionals (e.g. nurses) can be trained in their delivery [49,50,53,56,71]. This enables CBT programmes, including potential CBT programmes for treating obesity in adolescents, to be widely disseminated, increasing the availability of effective treatment programmes.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%
“…CBT treatments have the advantage over some other treatment approaches in that they are generally manual-based, meaning that non-psychologist health professionals (e.g. nurses) can be trained in their delivery [49,50,53,56,71]. This enables CBT programmes, including potential CBT programmes for treating obesity in adolescents, to be widely disseminated, increasing the availability of effective treatment programmes.…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%
“…Controlled studies showed that cognitive‐behavioural therapy (CBT; Latner et al, ; Latner & Wilson, ; Wilson, Fairburn, Agras, Walsh, & Kraemer, ), antidepressant medications (Agras et al, ), interpersonal psychotherapy (IPT; Agras, Walsh, Fairburn, Wilson, & Kraemer, ; Wilfley et al, ), group psychodynamic‐interpersonal psychotherapy (Tasca et al, ) and behavioural weight loss treatment (Marcus, Wing, & Fairburn, ) are effective in eliminating BE episodes and reducing associated psychopathology in the short and long term (Wilson, Grilo, & Vitousek, ). Unfortunately, these treatments have a limited effect on weight loss (Wilson & Shafran, ; Wilson, Wilfley, Agras, & Bryson, ).…”
mentioning
confidence: 99%
“…Psychotherapy (primarily CBT, DBT) (52) in diabulimia most often takes on the form of individual, group or family therapy (53). The results of the research indicate a greater effectiveness of a family therapy in comparison with an individual therapy, especially when the problem affects a child (54).…”
Section: Sorts Of Helpmentioning
confidence: 99%